Ionic strength-dependent changes in tentacular ion exchangers with variable ligand density. II. functional properties - Shambure, Rahul; Angelo, James M.; Gillespie, Christopher M.; Phillips, Michael; Graalfs, Heiner; Lenhoff, Abraham M. (Journal of Chromatography A, 2017)
The effect of ligand density was studied on protein adsorption and transport behavior in tentacular cation-exchange sorbents at different ionic strengths. Results were obtained for lysozyme, lactoferrin and a monoclonal antibody (mAb) in order to examine the effects of protein size and charge. The combination of ligand density and ionic strength results in extensive variability of the static and dynamic binding capacities, transport rate and binding affinity of the proteins. Uptake and elution experiments were performed to quantify the transport behavior of selected proteins, specifically to estimate intraparticle protein diffusivities. The observed trend of decreasing uptake diffusivities with an increase in ligand density was correlated to structural properties of the ligand-density variants, particularly the accessible porosity. Increasing the ionic strength of the equilibration buffer led to enhanced mass transfer during uptake, independent of the transport model used, and specifically for larger proteins like lactoferrin and mAb, the most significant effects were evident in the sorbent of the highest ligand density. For lysozyme, higher ligand density leads to higher static and dynamic binding capacities whereas for lactoferrin and the mAb, the binding capacity is a complex function of accessible porosity due to ionic strength-dependent changes. Ligand density has a less pronounced effect on the elution rate, presumably due to ionic strength dependent changes in the pore architecture of the sorbents. (C) 2017 Elsevier B.V. All rights reserved.